2017
DOI: 10.1063/1.4997266
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of drop impact on a superhydrophobic surface with macro-structures

Abstract: Drop-surface interaction is predominant in nature as well as in many industrial applications. Superhydrophobic surfaces show potential for various applications as they show complete drop rebound. In a recent work, it has been reported that the drop lift-off time on a superhydrophobic substrate could be further reduced by introducing a macro-ridge. The macro-ridge introduces asymmetry on the morphology of drop spreading and retraction on the surface. This changes the hydrodynamics of drop retraction and reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…21 Following this work, studies focused on contact time reduction by asymmetric dynamics have been carried out, including the inclined surface, 22,23 curved surface, [24][25][26][27][28][29][30] surfaces with macro structures of different geometries, [31][32][33][34][35][36][37][38][39][40] moving surfaces, 41,42 and off-center impact. 43,44 Besides the aforementioned asymmetric approaches, symmetric bouncing by involving the droplet center to retraction with point-like structure to reduce contact time has also been proposed. Liu et al fabricated convex surfaces with a height of 0.6 mm and a radius of 2.0 mm and found that such structures can reduce the contact time by 28.5%.…”
Section: Introductionmentioning
confidence: 99%
“…21 Following this work, studies focused on contact time reduction by asymmetric dynamics have been carried out, including the inclined surface, 22,23 curved surface, [24][25][26][27][28][29][30] surfaces with macro structures of different geometries, [31][32][33][34][35][36][37][38][39][40] moving surfaces, 41,42 and off-center impact. 43,44 Besides the aforementioned asymmetric approaches, symmetric bouncing by involving the droplet center to retraction with point-like structure to reduce contact time has also been proposed. Liu et al fabricated convex surfaces with a height of 0.6 mm and a radius of 2.0 mm and found that such structures can reduce the contact time by 28.5%.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic surfaces (HS) and superhydrophobic surfaces (SHS) possess some unique and practical properties such as surface cleaning, 17 anti-fouling, anti-icing, dropwise condensation 18 and drag reduction. 19 A superhydrophobic surface (SHS) is standardly defined as a surface with an equilibrium contact angle (CA) greater than 150˚ and very low (<10°) contact angle hysteresis (CAH). 20 The CAH, defined as the difference between the advancing and receding CA, is often used as a measure of drop mobility on a surface.…”
Section: Introductionmentioning
confidence: 99%
“…The stretch of the jet in the valley is dependent on the magnitude of the tangential momentum imparted to the drop. As w decreases, the spherical segment of the drop interacting with the inclined face increases producing higher tangential momentum (Regulagadda et al 2017). Secondary droplets are formed from the jet.…”
Section: Experimental Methodsmentioning
confidence: 99%